Dark Triad and Interpersonal Forgiveness: The Mediating Role of Interpersonal Relationship Satisfaction - Yaoguo Geng; Ziyang Cheng; Liping Shi; Tingting Zhan; Zhixia Hu; Wenjing Jin (Behavioral Sciences)
The social-emotional functions associated with the Dark Triad have been widely examined. However, further research is needed to explore the nuanced relationship between the Dark Triad and interpersonal relationships, particularly in diverse cultural contexts. This study aimed to investigate the relationship between the Dark Triad and interpersonal relationship satisfaction and interpersonal forgiveness by testing 577 students with the Dirty Dozen (DD), Interpersonal Relationship Satisfaction Questionnaire (IRSQ), and the Transgression-Related Interpersonal Motivations Scale-12-Item Form (TRIM-12). Results showed that (a) overall, the Dark Triad correlated negatively with lower interpersonal relationship satisfaction and interpersonal forgiveness. (b) Narcissism differs in the pattern of correlations from Machiavellianism and psychopathy. Machiavellianism and psychopathy were positively correlated with revenge, avoidance, and interpersonal dissatisfaction and negatively correlated with interpersonal satisfaction. In contrast, narcissism was positively correlated with revenge, avoidance, interpersonal dissatisfaction, and interpersonal satisfaction. (c) The mediating models showed that individuals with higher Dark Triad scores exhibited lower interpersonal relationship satisfaction and higher levels of revenge. Individuals with higher Machiavellianism and psychopathy showed greater interpersonal relationship dissatisfaction and more pronounced avoidance. These findings highlight the nuanced role of the Dark Triad in shaping interpersonal outcomes and suggest that targeted interventions focusing on relationship satisfaction and interpersonal forgiveness could mitigate the negative social behaviors associated with these traits.